Superhuman - Rowan Hooper (Little, Brown, 2018)
"Superhuman is a fascinating, eye-opening and inspiring celebration of the best that the current human species has to offer. This is a book about what it feels like to be exceptional - and what it takes to get there. Why can some people achieve greatness when others can't, no matter how hard they try? What are the secrets of long life and happiness? Just how much potential does our species have? In this inspirational book, New Scientist Managing Editor Rowan Hooper takes us on a tour of the peaks of human achievement. We sit down with some of the world's finest minds, from a Nobel-prize winning scientist to a double Booker-prize winning author; we meet people whose power of focus has been the difference between a world record and death; we learn from international opera stars; we go back in time with memory champions, and we explore the transcendent experience of ultrarunners. We meet people who have rebounded from near-death, those who have demonstrated exceptional bravery, and those who have found happiness in the most unexpected ways. Drawing on interviews with a wide range of superhumans as well as those who study them, Hooper assesses the science of peak potential, reviewing the role of genetics alongside the famed 10,000 hours of practice. For anyone who ever felt that they might be able to do something extraordinary in life, for those who simply want to succeed, and for anyone interested in incredible human stories, Superhuman is a must-read."--Provided by publisher.